2009
DOI: 10.1086/646609
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Elite Controllers, Viremic Controllers, and Long‐Term Nonprogressors in the US Department of Defense HIV Natural History Study

Abstract: Durable control of human immunodeficiency virus (HIV) replication and lack of disease progression in the absence of antiretroviral therapy were studied in a military cohort of 4586 subjects. We examined groups of elite controllers (ie, subjects with plasma HIV RNA levels of <50 copies/mL; prevalence, 0.55% [95% confidence interval {CI}, 0.35%-0.80%]), viremic controllers (ie, subjects with plasma HIV RNA levels of 50-2000 copies/mL; prevalence, 3.34% [95% CI, 2.83%-3.91%]), and subjects with a lack of disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
303
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(326 citation statements)
references
References 30 publications
14
303
3
6
Order By: Relevance
“…Our model offers a number of testable predictions: (i) There is a range of typical effector cell responses where PTC cannot be attained, no matter how small the viral reservoir. This regime describes most patients, because PTCs comprise 5-15% of the population (1) and elite controllers comprise <1% of the population (11,12). (ii) For individuals with responses in this regime, boosting their immune responses before termination of treatment may enhance the probability of post-treatment control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model offers a number of testable predictions: (i) There is a range of typical effector cell responses where PTC cannot be attained, no matter how small the viral reservoir. This regime describes most patients, because PTCs comprise 5-15% of the population (1) and elite controllers comprise <1% of the population (11,12). (ii) For individuals with responses in this regime, boosting their immune responses before termination of treatment may enhance the probability of post-treatment control.…”
Section: Discussionmentioning
confidence: 99%
“…1 do not appear to be ECs because they typically lacked protective HLA class I alleles-specifically, HLA-B*27 and B*57-that are generally overrepresented in ECs, as well as the strong HIV-specific immune responses found in most ECs (10). Further, ECs form only a fraction of a percent of the population (11,12), far less than the 5-15% of study patients found to be PTCs (1,2).…”
mentioning
confidence: 89%
“…1 These HIV controllers represent less than 5% of infected persons and are defined by their ability to maintain circulating virus loads at undetectable or very low levels. 2 Usually, but not always, controllers are also long-term nonprogressors, as defined by their ability to maintain normal CD4 ϩ T-cell counts and to remain clinically healthy for more than 10 years. 3,4 At the opposite end of the spectrum, HIV-infected noncontrollers have sustained high viral loads (Ͼ 10 000 copies/ mL) and usually experience disease progression, as defined by the loss of circulating CD4 ϩ T cells and the development of AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…A minority of individuals infected by HIV, denominated long term non-progressors (LTNP) remain healthy for more than 10 years without clinical evidence of disease progression 6,7 in the absence of combined antiretroviral therapy (cART). These cases, represented by approximately 5% to 15% of those infected 8 are characterized by stability or increase in CD4+ T count and strong response of cytotoxic T lymphocytes (CTL) against HIV, different to what occurs in TyP 9 .…”
mentioning
confidence: 95%